The influence of probiotics on bile acids in diseases and aging - Bhagavathi Sundaram Sivamaruthi (2020)
© 2020 The Author(s) Recent evidence indicates the use of probiotics in the prevention and treatment of diseases. Probiotics are capable of changing the gut microbiota composition and bile acid synthesis to elicit health benefits such as cholesterol-lowering, weight reduction, and improving insulin sensitivity. The aging population is prone to develop diseases because of their decreased physiological and biological systems. Probiotics are one of the promising supplements that may potentially counteract these detrimental effects. This review will discuss the influence of probiotics on bile acids in different populations-the elderly, obese individuals, and those with hypercholesterolemia, type 2 diabetes, hypertension, and non-alcoholic fatty liver disease.